Web-Based Contingency Management for Adolescent Tobacco Smokers: A Clinical Trial. Issue 3 (18th November 2018) - Harvanko, Arit; Slone, Stacey; Shelton, Brent; Dallery, Jesse; Fields, Sherecce; Reynolds, Brady
Abstract: Introduction: Adolescence is a critical time when the majority of tobacco users initiate smoking. Contingency management for adolescent smoking cessation has shown promise in previous studies, but efficacy following removal of contingencies is not well understood. This study examined a remote form of contingency management among non-treatment-seeking adolescent smokers. Methods: Participants ( N = 127) submitted breath carbon monoxide (CO) three times daily throughout a 42-day program. For this randomized trial, participants in the active condition ( n = 63) were reinforced for providing CO measurements on schedule and below a set criterion, whereas those in the control condition ( n = 64) were reinforced for providing CO measurements on schedule. Self-reported smoking and urinary cotinine levels were collected at several timepoints. Results: Active condition showed greater within-group reductions in CO levels relative to control condition, but not at 3- or 6-month follow-up. Active condition reported significantly less smoking during treatment compared to control condition, but not at follow-up. There were no significant differences for urinary cotinine. Overall treatment adherence was low, with only 37% and 51% of possible CO samples being submitted among active and control, respectively. Poor treatment adherence may explain the disparity between CO and cotinine results, and poor follow-up treatment efficacy. Conclusions: This study replicates feasibility of a remote form of contingency management for adolescent smoking. CO results suggest active condition reduced smoking within group, but treatment adherence and posttreatment efficacy was poor. Future research should focus on increasing adherence for this type of program among adolescent smokers. Implications: This study demonstrates feasibility of a remote form of contingency management therapy for smoking cessation among adolescents, while providing posttreatment efficacy data. Within-group efficacy of this form of treatment is suggested, but treatment adherence and follow-up efficacy were poor. This study underscores the need for further development of contingency management therapy for adolescent smoking cessation, which emphasizes better treatment adherence and posttreatment efficacy.